Efeitos da arrecadação tributária e dos gastos públicos em Serviços de saúde dos municípios de Pernambuco - Sousa, Kleber Morais de (2012)
This study aims to investigate the effects of municipal tax collection and polítical variables in the differenee of límit of 15% of spending with tax resources in the healthy services and aetions of municipalities from states of Pernambnco. The researeh is exploratory and used regression analysis with panel data as a quantitative method. It was made a data collection in the data banks of Ministry of Health, the National Treasury and the Supreme Electoral Tribunal referring to the 184 municipalíties, corresponding to the period of 2005 to 2009. It can be conc1uded that in election year there is an increase of 0,49% of healthy spending with tax resources and that there is a decrease of 0,63% in the differenee of applícation in mnnicipalities administered by party with the same affi1iation of the ruler. The per capita tax eollection, electoral competition for the office of mayor and party ideology of rulers do not affeet in the differenee of limit of 15% of expenditure with tax resources in healthy actions of Pernambuco' s municipalities.